Evaluation of the Anticancer Activity of a Bile Acid-Dihydroartemisinin Hybrid Ursodeoxycholic-Dihydroartemisinin in Hepatocellular Carcinoma Cells - Huang, Tzu-En; Deng, Yi-Ning; Hsu, Jui-Ling; Leu, Wohn-Jenn; Marchesi, Elena; Capobianco, Massimo L.; Marchetti, Paolo; Navacchia, Maria Luisa; Guh, Jih-Hwa; Perrone, Daniela; Hsu, Lih-Ching (Frontiers in Pharmacology, 2020)
Hepatocellular carcinoma (HCC) is the most common primary liver malignancy in adults and accounts for 85-90% of all primary liver cancer. Based on the estimation by the International Agency for Research on Cancer in 2018, liver cancer is the fourth leading cause of cancer death globally. Dihydroartemisinin (DHA), the main active metabolite of artemisinin derivatives, is a well-known drug for the treatment of malaria. Previous studies have demonstrated that DHA exhibits antitumor effects toward a variety of human cancers and has a potential for repurposing as an anticancer drug. However, its short half-life is a concern and may limit the application in cancer therapy. We have reported that UDC-DHA, a hybrid of bile acid ursodeoxycholic acid (UDCA) and DHA, is ~12 times more potent than DHA against a HCC cell line HepG2. In this study, we found that UDC-DHA was also effective against another HCC cell line Huh-7 with an IC50 of 2.16 μM, which was 18.5-fold better than DHA with an IC50 of 39.96 μM. UDC-DHA was much more potent than the combination of DHA and UDCA at 1:1 molar ratio, suggesting that the covalent linkage rather than a synergism between UDCA and DHA is critical for enhancing DHA potency in HepG2 cells. Importantly, UDC-DHA was much less toxic to normal cells than DHA. UDC-DHA induced G0/G1 arrest and apoptosis. Both DHA and UDC-DHA significantly elevated cellular reactive oxygen species (ROS) generation but with different magnitude and timing in HepG2 cells; whereas only DHA but not UDC-DHA induced ROS in Huh-7 cells. Depolarization of mitochondrial membrane potential was detected in both HepG2 and Huh-7 cells and may contribute to the anticancer effect of DHA and UDC-DHA. Furthermore, UDC-DHA was much more stable than DHA based on activity assays and HPLC-MS/MS analysis. In conclusion, UDC-DHA and DHA may exert anticancer actions via similar mechanisms but a much lower concentration of UDC-DHA was required, which could be attributed to a better stability of UDC-DHA. Thus, UDC-DHA could be a better drug candidate than DHA against HCC and further investigation is warranted.